Characterization and Release Studies of Liposomal Gels Containing Glutathione/Cyclodextrins Complexes Potentially Useful for Cutaneous Administration. Issue 4 (15th February 2014) - Cutrignelli, Annalisa; Lopedota, Angela; Denora, Nunzio; Laquintana, Valentino; Tongiani, Serena; Franco, Massimo
<x xml:space="preserve">Abstract</x> The aim of this work is to develop and characterize a formulation intended for the cutaneous administration of glutathione (γ‐glutamylcysteinylglycine, GSH), potentially useful for cellular defense against UV‐induced damage. For this purpose, liposomes containing GSH or GSH/cyclodextrins(CDs) inclusion complexes as well as liposomes dispersed within a hydrophilic gel, were evaluated. These formulations were designed in order to obtain a system combining the advantages of liposomes as vehicles for topical drug delivery with those of CDs as penetration enhancers. The studied CDs were the natural (β‐CD) and chemically modified (i.e., HP‐β‐CD and CH3‐β‐CD) cyclodextrins. The prepared liposomes showed homogeneous size distribution, mean diameter in the range 622–1435 nm, small positive charge (+3.1 to +6.6 mV), and encapsulation efficiency of the peptide in the range 13.6%–23.7%. Release studies showed that the presence of the oligosaccharide may influence to some extent the amount of drug released, whereas stability studies clearly point out that the incorporation in a hydrophilic gel of 2‐hydroxyethylcellulose insures a stable formulation maintaining unchanged the characteristics of liposomal vesicles. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1246–1254, 2014